1981
DOI: 10.1073/pnas.78.12.7294
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic glycopeptide substrates for receptor-mediated endocytosis by macrophages.

Abstract: Mammalian macrophages contain a transport system that binds and internalizes glycoproteins with exposed mannose residues. This system and analogous systems on other types of cells require substrates to bear multiple nonreducing terminal residues ofthe appropriate sugar for effective uptake. Small multivalent synthetic glycopeptides with mannose residues covalently linked through a spacer arm to the a-and e-amino groups of lysine, dilysine, and trilysine are competitive inhibitors of rat alveolar macrophage upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Since preliminary binding studies revealed that the affinity of 4-aminophenyl-␣-D-mannopyranoside is only slightly higher than that of ␣-D-mannose (K i (app) ϭ 1.8 mM, log(IC 50 ) ϭ Ϫ2.48 Ϯ 0.01; data not shown), we assume this to be unlikely. An alternative explanation is that the (p-hydroxyanilino)carbamide spacer is longer (2 Å) than the thioproprionyl spacer used by Robbins et al (29). Recent studies by Biessen et al (31) have already emphasized the relevance of optimal spacing of terminal glycosides to achieve avid recognition by a comparable eukaryotic lectin, the asialoglycoprotein receptor.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Since preliminary binding studies revealed that the affinity of 4-aminophenyl-␣-D-mannopyranoside is only slightly higher than that of ␣-D-mannose (K i (app) ϭ 1.8 mM, log(IC 50 ) ϭ Ϫ2.48 Ϯ 0.01; data not shown), we assume this to be unlikely. An alternative explanation is that the (p-hydroxyanilino)carbamide spacer is longer (2 Å) than the thioproprionyl spacer used by Robbins et al (29). Recent studies by Biessen et al (31) have already emphasized the relevance of optimal spacing of terminal glycosides to achieve avid recognition by a comparable eukaryotic lectin, the asialoglycoprotein receptor.…”
Section: Discussionmentioning
confidence: 96%
“…Oshimi et al (28) demonstrated that the affinity of tris(hydroxymethyl)-based mannosides was only slightly higher than that of bi-and monosubstituted analogues, which was attributed to the suboptimal valency and spacing of the terminal mannosyl groups (ϳ9 Å) within the mannose clusters. The di-, tri-, and tetramannosides synthesized by Robbins et al (29) displayed higher, yet micromolar, affinities for the mannose receptor. Since the latter mannosides contained the same oligolysine backbone as our mannosides, their lower affinity is probably caused by differences in the chemical nature and the length of the spacers connecting the terminal 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several glycosylated lysine and lysine containing peptides are reported in the literature [19][20][21] and more specifically, the interaction of 3 and its galactose analog with macrophages and HepG2 cells has been described [22,23]. This background provided us an impetus to investigate self-assembly properties of mannosylated 3.…”
Section: Resultsmentioning
confidence: 96%
“…However, the seminal discovery of the mannose-binding lectin of the macrophage by Philip Stahl et al109 at Washington University, St Louis, MI, was the critical breakthrough. This revelation focused attention on delivery of proteins to be explored for therapeutic purposes in Gaucher disease – in which the prime cellular target is the eponymous macrophage 110. In vivo and laboratory studies also carried out at this time in St Louis by William Sly and colleagues (see Achord et al111) with different glycoforms of acid β-glucuronidase, which is deficient in the lysosomal disease mucopolysaccharidosis type 7 (Sly disease), led to the practical realization that the mannose/lectin receptor could be utilized efficiently to target human glucocerebrosidase to macrophages in Gaucher disease after modification of its carbohydrate residues.…”
Section: Easy Concepts and Trialsmentioning
confidence: 99%